FACTORS INFLUENCING ADHERENCE TO TAKING ANTIRETROVIRAL MEDICATION IN PEOPLE WITH HIV/AIDS AT THE WAENA COMMUNITY HEALTH CENTER, JAYAPURA CITY - B. Hutadjulu, Marlina; Tuturop, Katarina Lodia; Adimuntja, Natalia Paskawati; Bouway, Dolfinus Yufu; Yufuai, Agustina Regina; Pariaribo, Konstantina Marthina (HEARTY, 2024)
HIV/AIDS is an infectious disease that is still a global health problem today. Efforts to prevent high transmission are by taking antiretroviral medication (ARV) to weaken the virus and improve the quality of life for people living with HIV/AIDS (PLWHA). Therefore, the level of adherence to taking ARV medication is important for PLWHA patients. The aim of this study was to determine the factors that influence adherence to ARV medication in PLWHA patients at the Waena Health Center, Jayapura City. The type of research used is observational analytical designcross sectional study. The population of PLWHA patients taking ARV medication was 82 people with sample collection using a saturated sampling technique. Data was obtained using a questionnaire and data analysis was carried out usingchi square test. The research results showed that the majority of PLWHA patients were aged 25-35 years, 41 people (50.0%), 46 people (56.1%), with the highest marital status, namely unmarried, 70 people (85, 4%), 59 people (72%) had higher education and 53 people (64.6%) worked. There were 46 patients (56.1%) who were compliant with taking ARV medication and 36 people (43.9%) were non-compliant. There was an influence of length of treatment (ρ-value = 0.006 < 0.05; RP = 2.161; CI95% (1.42-3.3), knowledge (ρ-value = 0.035 < 0.05; RP = 1.789; CI95% (1.09-2.94), and attitude (ρ-value = 0.013 < 0.05; RP = 1.953; CI95% (1.202-3.172) with adherence to taking ARV medication in PLWHA patients at the Waena Health Center, Jayapura City. In addition, it is known There was no influence of family support for PLWHA patients on adherence to ARV medication in PLWHA patients at the Waena Community Health Center, Jayapura City (ρ-value = 0.930 > 0.05; RP = 0.930; CI95% (0.561-1.56).